2000
DOI: 10.2174/1381612003400533
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Cytokines and Cytokine Antagonists

Abstract: Cytokines are critical mediators of protective host responses, including defense against microbial invasion and tumorigenesis. However, the production of specific proinflammatory cytokines must be tightly regulated and compartmentalized to prevent the overzealous expression of these molecules that can culminate in unabated inflammation and tissue injury. Cytokine production and/or biologic effects can be inhibited by a variety of endogenous molecules, including anti-inflammatory cytokines, soluble cytokine rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 92 publications
3
37
0
Order By: Relevance
“…TNF-α was significantly increased in E. coli infected group comparing with the control one. This result goes with Theodore [29] who recorded the most marked acute phase reactions in responses to E. coli are the greatest TNF-α responses in blood plasma. This result also agreed with Zimecki et al [30] who reported that I.V.…”
Section: Groups T Protein Gm/dl Albumin Gm/dl α-Globulin Gm/dl β-Glosupporting
confidence: 76%
“…TNF-α was significantly increased in E. coli infected group comparing with the control one. This result goes with Theodore [29] who recorded the most marked acute phase reactions in responses to E. coli are the greatest TNF-α responses in blood plasma. This result also agreed with Zimecki et al [30] who reported that I.V.…”
Section: Groups T Protein Gm/dl Albumin Gm/dl α-Globulin Gm/dl β-Glosupporting
confidence: 76%
“…This cytokine is also believed to play an important pathogenic role in type 1 autoimmune diseases (1). Thus, therapeutic modalities based on anti-TNF-α have been developed to treat these conditions (2). On the other hand, TNF-α is also involved in type 1 cell-mediated immune responses to intracellular pathogens such as mycobacteria (3).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IL-10 inhibits the surface expression of major histocompatibility complex class II molecules, nitric oxide synthesis, and NF-B nuclear translocation after LPS stimulation and causes the down-regulation of TNF-␣ receptors (16,19,35). Studies have identified IL-10 to be an important regulator of inflammation in a variety of inflammatory disease states, including sepsis (28). For example, increased blood IL-10 levels are found in septic patients, as well as healthy subjects challenged with endotoxin intravenously (21,31).…”
mentioning
confidence: 99%